2015
DOI: 10.1039/c4ta03968h
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, thermal, and electronic responses of small-molecule-loaded metal–organic framework materials

Abstract: We combine infrared spectroscopy, nano-indentation measurements, and ab initio simulations to study the evolution of structural, elastic, thermal, and electronic responses of the metal organic framework MOF-74-Zn when loaded with H2, CO2, CH4, and H2O. We find that the molecular adsorption in this MOF triggers remarkable responses in all of these properties of the host material, with specific signatures for each of the guest molecules. With this comprehensive study we are able to clarify and correlate the unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 66 publications
4
47
0
Order By: Relevance
“…They established the main necessary and sufficient conditions of mechanical stability known as the Born criteria . Subsequently, many researchers have used alternative conditions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They established the main necessary and sufficient conditions of mechanical stability known as the Born criteria . Subsequently, many researchers have used alternative conditions …”
Section: Resultsmentioning
confidence: 99%
“…Such a condition turns out to be necessary but not sufficient . In such cases, the Fedorov criteria leads to incorrect conclusions concerning the mechanical stability of systems, such as MOF‐74 materials with CH 4 molecules …”
Section: Resultsmentioning
confidence: 99%
“…In particular, it explains the MOF softening upon adsorption found (but not commented upon) by Canepa et al in their ab initio studies of CO2 and CH4 adsorption in MOF-74-Zn. 35 It can also help explain the recent counter-intuitive experimental results of Alabarse et al, who showed that the presence of water within the pores of AlPO4-54 lead to a decrease in mechanical stability, attested by the occurrence of pressure-induced amorphization at lower pressure than in the guest-free AlPO4-54. 46 This last example shows the importance of better understanding the influence of guest adsorption on mechanical properties of microporous materials, as it can have a drastic impact not only on the modification of the elastic behavior (thus augmenting, through soften- ing, the magnitude of adsorption deformation) but also on the stability under pressure, a key property for many industrial applications.…”
mentioning
confidence: 87%
“…This range agrees favourably with the thickness calculated for the optimised 2100-droplet ZIF-8-MSS, which is 10.4 m (see ESI † Section S14). FEA further indicates that it takes a strain of 1  10 -4 -2  10 -4 in a ZIF-8-MSS with such a thickness to generate the range of observed responses, i.e., [1][2][3][4][5][6][7][8][9][10]. For example, methanol induces an output voltage of 10 mV in the 2100-droplet sensor (Fig.…”
Section: Detection Limitsmentioning
confidence: 99%